2020
DOI: 10.1007/s10616-019-00367-6
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of calcium-induced differentiation potential and tight junction formation in HaCaT keratinocytes by functional attenuation of overexpressed high mobility group box-1 protein

Abstract: HaCaT cells have been widely used as undifferentiated epidermal keratinocytes, since these non-tumorigenic cells can be readily maintained in conventional medium and partly retain epidermal differentiation potential upon stimulation with high concentration of calcium. In contrast to primary epidermal keratinocytes, however, these cells never form tight junction (TJ), a specific structure in highly differentiated keratinocytes, solely by the differentiation stimulation. Here, we show that HaCaT cells secrete a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(44 reference statements)
0
1
1
1
Order By: Relevance
“…8B). 37–39 In contrast, we demonstrated GL's TJ-opening activity, which is apparently in opposition to its reported protective function (Fig. 8A).…”
Section: Discussioncontrasting
confidence: 89%
“…8B). 37–39 In contrast, we demonstrated GL's TJ-opening activity, which is apparently in opposition to its reported protective function (Fig. 8A).…”
Section: Discussioncontrasting
confidence: 89%
“…The induction of G1 arrest and cell cycle exit account for the observed effects on cell proliferation. In terms of differentiation, although HaCaT cells maintained for a long period in conventional high-calcium medium retain their differentiation potential 39 , 40 and mesotrypsin diminishes the abundance of the differentiation marker Pro-FLG (Fig. 3 ), the expression of canonical differentiation markers, including TGase1, Loricrin, and Involucrin, remains unaffected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the diverse biological functions of PAX6, HMGB1, and NFE2, data concerning the involvement of these TFs in the context of keratinocyte differentiation is still very limited. To our knowledge, the link between HMGB1 and cell differentiation was evidenced in only one study which demonstrated that the functional ablation of secreted HMGB1 results in aberrant HaCaT differentiation [45]. Additionally, NFE2 was shown in several studies to activate antioxidant enzymes to protect skin keratinocytes against oxidative damage during differentiation [46][47][48].…”
Section: Discussionmentioning
confidence: 99%